Dasar dan sistem media di Indonesia 1966-1998 - Erman Anom (Universiti Kebangsaan Malaysian, 2010)
This study looks into how the press system under Soeharto’s political system is developed to the extent that it is referred as the Indonesian press policy between 1966 and 1998. To achieve the purpose of the study, an analysis is done on the press system or factors influencing the formation of the press system by utilising the historical approach through documents analyses and in-depth interviews. The findings of the study revealed that the formation of the press system under the leadership of Soeharto is a conscious process planned according to the philosophy and values practiced by Soeharto which later became the Indonesian national policy. This planned process is based on the cultural values of “gotong-royong”, the spirit of harmony, compatibility, balance and obedience. The process of press system formation is done through persuasion and consensus during meetings and the results of which are used as tools to control press activities in Indonesia. The study also found that several dominant factors whicsh have influenced the development of the press system include socio-cultural factor, politics and economy. The findings showed that from 1966 to 1973, Soeharto’s government had aspired to build a healthy, free and accountable press system and promote a brotherhood spirit in relation to the direction of the government’s political ideology plan. From 1974 to 1983, the development and growth of the press are based on the spirit and enthusiasm of Pancasila, with the aim to support the development of a Pancasila society which will lead to a positive interaction among the government, press and society. From 1984 to 1998, the press publication licence (SIUPP) became the strength in the development of the commercial press which has led to the mushrooming of a free and accountable press. These are the policies which later became an important platform in the formation of a Pancasila-based press system under Soeharto’s leadership.